Laboratuvar iklimlendirmesi ve optimum kontrol - Sözer, Kadri (Fen Bilimleri Enstitüsü, 1996)
Günümüzde üretim ve imalatta kalite kontrolün öneminin artması ile birlikte, metroloji ve kalibrasyon laboratuvarlarına olan ihtiyaç oldukça artmıştır. Laboratuvarların iklimlendirilmesi ile sağlanan ortam şartları, yapılan ölçümlerin doğruluğu ile direk olarak ilgilidir. Bunun yanısıra, iklimlendirme sisteminin dizaynında nem ve sıcaklık değişkenlerinin birbirlerine olan etkilerinin gözönünde bulundurulması, enerji kayıplarını azaltacağı gibi sistemin optimum kontrolünü de sağlayacaktır. Bu çalışmada bu iki konu ayrı ayrı incelenmektedir. Tezin 1. kısmını oluşturan 2. bölümde, ölçme ve kalibrasyon laboratuvarlarının iklimlendirme sistemleri tasarlanırken, hava kalitesi, hava hızı, hava akış şekli, sıcaklık, nem gibi paremetrelerin seçilmesi konusu incelenmiştir. Bu amaçla, labaratuvar iklimlendirilmesinde çok sık kullanılan temiz oda standartlarından da bahsedilmiş ve ihtiyaç duyulan temiz oda klasının elde edilebilmesi için kullanılması gereken filtrelerin seçimi de incelenmiştir. 3., 4. ve 5. bölümlerde Ulusal Metroloji Enstisünde kurulu olan kütle labaratuvarı kontrol hacmi olarak seçilerek, kontrol hacmi ve kurulu olan klima sistemi tanıtılmış ve daha sonra kontrol hacminin matematik modeli kurularak çözülmüş ve bilgisayar çözümleri deney sonuçları ile karşılaştırılmıştır. Kontrol hacmi fanının iki farklı devirde çalıştırılmasıyla elde edilen bilgisayar çözümlerinin, deneysel olarak bulunan çözümlere oldukça yakın eğriler izledikleri görülmüştür.

Part 1. Introduction : With growing technology, the assurance of measurement in production and quality has become universally influential. The accuracy of the measurement is crucial to the condition and quality of air in the place where it is done. in the air conditioning of offıces and houses, it is enough for people to feel comfortable; neither too höt nor cold. However, in the calibration and measurement laboratories, a lot of parameters, primarily temperature and humidity control should be obtained to achieve accurate measurement. in addition to this, it is desirable to accomplish the design of air conditioning system with minimal energy too. When we consider that, at least %25 of the world energy consumption is used for heating and cooling of the buildings [1], we can understand how important it is to economize on energy. As it is known, temperature and relative humidity are related to each other in the process of air conditioning. The affection of these two parameters with each other should be considered in the design of air conditioning systems. Otherwise, it can cause vibration and energy loses in the system. This thesis has göt two main stages including the following two subjects. in the first stage, the criteria of designing air conditioning systems for laboratories, which consists of temperature, humidity, air quality, air flow patterns, air velocities, noise, pressurization ete. is examined. Although there isn't any standard for measurement and calibration laboratories, the clean room classes can partially assist. Therefore, the clean room classes and also filtering systems to attain. these classes are examined. xi in the second stage, the Mass laboratory which was established in Ulusal Metroloji Enstitüsü was selected as the control chamber and the mathematical model, which consists of temperature and humidity relations, is verified. in the installation of the model, models established by Parmaksızoğlu [1] and Öznergiz [2] facilitate me. Following this, the mathematical model is solved by computer and the results are compared with the experiments from the real system. Part 2. Air Conditioning Systems of Measurement and Calibration Laboratories : in this part of the thesis, parameters f ör designing air conditioning system of laboratories are examined. The main parameters are temperature and relative humidity. A lot of devices in laboratories are sensitive to these parameters. For example, metal parts expand and shrink, zener diode voltage value decrease ör increase with changing temperature. in addition to this, when relative humidity is very Iow, it can cause static electric loads for electronic devices. Air flow patterns and air velocities are other important parameters which should be considered in the design of air conditioning systems. Basically, there are two different air flow patterns; non laminar flow and laminar flow. in the latter, the air moves with uniform velocity along parallel flow lines, with a minimum of eddies. However, in non laminar flow, air moves with nonuniform air patterns. Air velocities for nonlaminar air flow should be between 0.15- 0.45 m/san. Lower velocities may permit particles to settle and higher velocities may generale objectionable local turbulence and drafts. in a laminar flow system, air is introduced evenly from öne entire surface of room, such as ceiling ör a wall, with flow at constant velocity across the room and removed through the enter area of an opposite surface. To provide good dilution and sufficient air motion to prevent settling of particles, velocity should be about 0.45 m/san. [9] Noise and pressurization control are also important for the laboratories too. For normal applications, the noise level is designed to be belovv 65 decibels [9]. Laboratories should be maintained at static pressure suffıciently higher than xii atmospheric pressure to prevent infîltration by wind ör other effects. Another essential criteria, which should be controlled, is airborne particles in the air. Clean room classes assist to define the quality of air in the laboratories. The first Clean room standard was introduced with American Federal Standard 209 in 1963. After that, this standard was improved and 209-D in 1988 and 209-E in 1992 were issued. Another standard widely used is the German VDI-2083 which is devised by considering Fed. Std. 209-D. Although 209-E is the last version of Fed. Std. 209, 209-D is commonly known and used. Classes in this standard are classifıed class l, 10, 100, 1.000, 10.000 and 100.000, which are based on partide count with maximum number of particles, 0.5 microns and larger. For example, in class 100.000, partide count must not exceed 3.530.000 partide per m3 ( 100.000 particles per ft3) of a size 0.5 microns and larger. Before selecting the clean room class for calibration and measurement laboratories, a decision must be made to how critical this particulate matter is to the process. To achieve the clean room class selected, necessary type of fılters should be used in the air conditioning system. The basic types of air fılters in use today are straining, impingement, interception, diffusion and electrostatic. The basic parameter for choosing filters is their efficiency. Standards used to classify the effıciency of the fılters are ASHRAE 52-76 and EUROVENT 4/5. in these standards, there are two definitions named Weight Arrestance and Atmospheric Dust Spot Efficiency. According to the efficiency of the filters, they are named EU2, EU3 ete. If the efficiency of the filler is more than % 98, DOP test ( Dioctyl Phthalate ) is applied. The filler which has göt DOP effıciency more than %99.97 is called HEPA filler ( High Efficiency Particulale Air Filler ) Part 3. Description of the System That is Controlled : in this part of the thesis, control chamber, which is Mass laboratory established in Ulusal Metroloji Enstitüsü and the central air conditioning system which comprises whole air conditioning units of laboratories, fresh air unit and ehiller units are described. xiii considering thermal storing properties of walls. This enables one to understand the effect of this property in the computer solution. Part 4. Solving the Mathematical Model with Computer and Comparing the Solutions with Experimental Results : In this part, non linear differential equations including temperature, absolute humidity and leakage heat, are solved by using Mathematica Version 2 program and the results are compared with experimental results. Two solutions are obtained by making the fan work at stepl and step2. At the same time, the control chamber is humidified with the fresh air. These solutions are: 1- Fan works in the second step W(0) = 4 gr/kg ( absolute humidity of control chamber at t=0 ) Wa =8 gr/kg ( absolute humidity of fresh air ) T(0) = 20°C ( temperature of control chamber at t=0 ) Ta = 18°C ( temperature of fresh air ) Q =1.8kW ( supplied heat ) cia =0.15 mVsan ( fresh air quantity ) 2- Fan works in the first step W(0) = 4 gr/kg q, = 0.0925 mVsan Wa =8 gr/kg T(0) = 20°C Ta = 18°C Q = 0.8 kW The computer solutions and experiments are done in 2°C outside temperature. So it is expected that the soil temperature under the floor is 10°C and near the wall is 4°C. [16] XVI Part 7. Conclusion and Advice : In this part, firstly, the main parameters which should be considered for designing the air conditioning systems of measurement and calibration laboratories are advised. After that, the comparison of computer solutions with the experimental results is discussed. It is found that, the variation curves of temperature and absolute humidity, found by computer simulation, is very near to the experimental results. xvn considering thermal storing properties of walls. This enables one to understand the effect of this property in the computer solution. Part 4. Solving the Mathematical Model with Computer and Comparing the Solutions with Experimental Results : In this part, non linear differential equations including temperature, absolute humidity and leakage heat, are solved by using Mathematica Version 2 program and the results are compared with experimental results. Two solutions are obtained by making the fan work at stepl and step2. At the same time, the control chamber is humidified with the fresh air. These solutions are: 1- Fan works in the second step W(0) = 4 gr/kg ( absolute humidity of control chamber at t=0 ) Wa =8 gr/kg ( absolute humidity of fresh air ) T(0) = 20°C ( temperature of control chamber at t=0 ) Ta = 18°C ( temperature of fresh air ) Q =1.8kW ( supplied heat ) cia =0.15 mVsan ( fresh air quantity ) 2- Fan works in the first step W(0) = 4 gr/kg q, = 0.0925 mVsan Wa =8 gr/kg T(0) = 20°C Ta = 18°C Q = 0.8 kW The computer solutions and experiments are done in 2°C outside temperature. So it is expected that the soil temperature under the floor is 10°C and near the wall is 4°C. [16] XVI Part 7. Conclusion and Advice : In this part, firstly, the main parameters which should be considered for designing the air conditioning systems of measurement and calibration laboratories are advised. After that, the comparison of computer solutions with the experimental results is discussed. It is found that, the variation curves of temperature and absolute humidity, found by computer simulation, is very near to the experimental results.
Air conditioning of lâboratordes and optimum control
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1996
Keywords: Laboratuvarlar; Meteoroloji; Laboratories; Meteorology